Exports and Productivity : Comparable Evidence For 14 Countries (The World Bank, 2007)
The authors use comparable micro level panel data for 14 countries and a set of identically specified empirical models to investigate the relationship between exports and productivity. The overall results are in line with the big picture that is by now familiar from the literature: Exporters are more productive than non-exporters when observed and unobserved heterogeneity are controlled for, and these exporter productivity premia tend to increase with the share of exports in total sales; there is strong evidence in favour of self-selection of more productive firms into export markets, but nearly no evidence in favour of the learning-by-exporting hypothesis. The authors document that the exporter premia differ considerably across countries in identically specified empirical models. In a meta-analysis of their results the authors find that countries that are more open and have more effective government report higher productivity premia. However, the level of development per se does not appear to be an explanation for the observed cross-country differences